Route Optimization of Oil Country Tubular Goods Distribution Using Sweep and Savings Algorithm - Gita Kurnia; Adji Chandra Kurniawan; Maulida Nawadir; Maghfira Safitri Yasmin; Marlene Hibatullah (IPTEK Journal of Proceedings Series, 2020)
In the oil and gas industry, one of the key activities is the drilling process where the oil or natural gas are extracted. The process requires the supply of rolled products known as the Oil Country Tubular Goods (OCTG). As an important drilling component, OCTG has a high demand, which in some case it is not balanced with the optimal distribution route and cost that may affect the industry’s profit. In order to obtain the optimal distribution routes, this research compares transport routes generated by Sweep and Savings Algorithm to solve the Capacitated Vehicle Routing Problem, by taking an oil and gas company with inefficient OCTG distribution in Sumatera as the object of the study case. Additionally, the total transportation cost is calculated to further compare the results. The research concludes that Sweep Algorithm produces the most efficient routes with the lowest total transportation cost of Rp.18,890,875,000 per year, or 24% less than total cost derived from Savings Algorithm route.